Drainage Design for a Freeway to Counter Water Infiltration Effects - Asadi, Hossein; Asadi, Alireza; Ghadimi, Behzad; Nikraz, Hamid (Research Publishing Services, 2012)
The very serious deteriorations that have occurred in the pavement structure of the Azadegan freeway has resulted in a failure to operate under heavy traffic load. Since this road is one of the most demanding accesses to absorb the traffic from cities in the neighborhood of Tehran (capital city of Iran) Isfahan and Shiraz it was very crucial to solve the problem as soon as possible. For this reason the first step was addressing the main causes of deteriorations by conducting a comprehensive survey on this matter. This paper discusses the design of a proper drainage system for the Azadegan freeway in two steps; Firstly designing a proper drainage system for removing the water run-off from pavement surface and secondly designing an appropriate drainage system to remove the infiltrated water from surface cracks to sub-layer structure. Finally the results will be declared and discussed.